國小行政人員感知到職前訓練與工作需求的能力落差之研究 Perceived Competency Disparities between Pre-service Training and Job Demands of - 洪榮昭 Jon-Chao Hong; 黃明月 Ming-Yueh Hwang; 許伶琦 Lin-Chi Hsu; 李嘉崑 Chia-Kun Lee (National Taiwan Normal University, 2009)
本研究旨在探討行政人員之教育訓練是否能培訓其校園行政管理的知識與技能，以應付當前學校行政的工作需求。在研究中，共有1,872位國小行政人員接受問卷調查，該問卷共計有44題，分為六大類，藉此來瞭解行政主管對能力落差的看法。此樣本包括來自全國的國小校長、主任及組長級行政人員，問卷回收率達43.59%，計有816 份進行分析處理。研究結果發現，這些行政人員對問卷中六類能力落差的感受多偏於中低程度，而這些學校創新管理的能力中，心智能力是最被注重，而專業能力是最少被提及。 The aim of this study is to explore whether school administrators' training has provided necessary knowledge and competency for school management, which allows school administrators to cope with current demands in their profession. This study also examines competency disparities based on a survey. The 44-item, 6-category survey was then distributed to a sample of 1,872 elementary school administrators. These subjects consisted of nationwide elementary school principals, managers and team leaders. A return rate of 43.59% was achieved and 816 valid samples were collected and analyzed. The results indicated a common trend in all 44 items. The findings suggested that: perceptions of competency disparity in the six categories drawn from primary school administrators ranged from the low to the intermediate level. Among the six categories of elementary school administrators' competencies in school innovative management, "mental capability" was most significantly perceived and "professional capability" was least mentioned.